Adapting and implementing training, guidelines and treatment cards to improve primary care-based hypertension and diabetes management in a fragile context: results of a feasibility study in Sierra Leone - Guanyang Zou; Sophie Witter; Lizzie Caperon; John Walley; Kiran Cheedella; Reynold G. B. Senesi; Haja Ramatulai Wurie (BMC, 2020)
Abstract Background Sierra Leone, a fragile country, is facing an increasingly significant burden of non-communicable diseases (NCDs). Facilitated by an international partnership, a project was developed to adapt and pilot desktop guidelines and other clinical support tools to strengthen primary care-based hypertension and diabetes diagnosis and management in Bombali district, Sierra Leone between 2018 and 2019. This study assesses the feasibility of the project through analysis of the processes of intervention adaptation and development, delivery of training and implementation of a care improvement package and preliminary outcomes of the intervention. Methods A mixed-method approach was used for the assessment, including 51 semi-structured interviews, review of routine treatment cards (retrieved for newly registered hypertensive and diabetic patients from June 2018 to March 2019 followed up for three months) and mentoring data, and observation of training. Thematic analysis was used for qualitative data and descriptive trend analysis and t-test was used for quantitative data, wherever appropriate. Results A Technical Working Group, established at district and national level, helped to adapt and develop the context-specific desktop guidelines for clinical management and lifestyle interventions and associated training curriculum and modules for community health officers (CHOs). Following a four-day training of CHOs, focusing on communication skills, diagnosis and management of hypertension and diabetes, and thanks to a CHO-based mentorship strategy, there was observed improvement of NCD knowledge and care processes regarding diagnosis, treatment, lifestyle education and follow up. The intervention significantly improved the average diastolic blood pressure of hypertensive patients (n = 50) three months into treatment (98 mmHg at baseline vs. 86 mmHg in Month 3, P = 0.001). However, health systems barriers typical of fragile settings, such as cost of transport and medication for patients and lack of supply of medications and treatment equipment in facilities, hindered the optimal delivery of care for hypertensive and diabetic patients. Conclusion Our study suggests the potential feasibility of this approach to strengthening primary care delivery of NCDs in fragile contexts. However, the approach needs to be built into routine supervision and pre-service training to be sustained. Key barriers in the health system and at community level also need to be addressed.